Morfologi Akulturatif Rumah Bangun Gudang: Integrasi Vernakular Banjar, Kolonial, dan Islam di Sungai Jingah - Rafika Amelia Fitri; Zulfa Jamalie (MAN 4 Kota Pekanbaru, 2026)
The Sungai Jingah area in Banjarmasin is one of the historic residential areas that preserves a wealth of vernacular architecture, one of which is the Bangun Gudang house type. This study aims to identify and describe the forms of cultural acculturation represented in the morphology of the building. The research method used is descriptive qualitative with a case study approach through field observation. The results show that the Bangun Gudang House in Sungai Jingah is not merely a functional building used as a residence and storage for trade goods, but rather a product of a complex cultural synthesis. Acculturation is clearly visible in the combination of Banjar architectural structures and Colonial architectural elements (hipped/pyramidal roof forms, symmetrical spatial organization, and decorative ornamental details). Strong religious values are also integrated through Islamic architecture, manifested in the form of carved Qur’anic calligraphy on the inner window elements as symbols of prayer and protection. This combination reflects the identity of the Sungai Jingah community as religious yet open to external influences. These findings emphasize the importance of preserving traditional houses as cultural artifacts that contain spiritual and historical messages.